Quality of Synthesized Speech: Impact of the Newest Coding Approaches - Miroslava Mrvova; Peter Pocta (Communications - Scientific letters of the University of Zilina, 2011)
This contribution deals with the issue of quality of synthesized speech. It introduces principles and approaches of creating this type of speech and basic methods and techniques used to assess the quality of synthesized speech. This article also offers a short overview of relevant experimental studies discussing issues related to this kind of speech and its quality assessment. Finally, it investigates effect of the newest coding approaches (e.g. Speex, iLBC, EVRC-B, etc.) on quality of naturally-produced speech and synthesized speech (generated by diphone and unit-selection synthesizers) predicted by two different objective models and provided by subjective tests.